Wideband LNA optimal sizing using an Optimization Platform, based on Cadence - Gonçalves, Diogo José Fernandes (2020)
In this thesis an Optimization Platform capable of guaranteeing a proper sizing for a Low Noise Amplifier, is proposed. The developed platform, which runs in a python client, contains a Genetic Algorithm capable of managing the circuits’ components dimensions, to fulfill the necessary requirements imposed by high- frequency architectures. To improve the results, the Cadence simulator is used, guaranteeing a more accurate simulation process when compared to traditional sizing methods. The Optimization Platform contains an interface, which provides different optimization methods, each one with different approaches to provide the circuits’ optimal sizing.